The moderating effect of institutional quality on the relationship between financial inclusion and the profitability of commercial banks in selected ASEAN-5 countries: An analysis - Balboa, Miguel Rene Q. (Animo Repository, 2023)
Financial inclusion is a subject that has been on the rise recently. One specific topic that has been the subject of many previous studies is how it affects bank profitability, though there is yet to be a final conclusion on this. Moreover, institutional quality has been known to have its own effects on financial inclusion, but research on its impact on bank profitability has been scarce, and how it moderates the financial inclusion-bank profitability relationship has yet to be seen. The researchers aim to contribute to the literature on institutional quality, financial inclusion, and bank profitability, providing insights for future researchers who are seeking to enhance financial sector performance and study it within a deeper context. This study used composite indexes of financial inclusion and institutional quality, tested using Ordinary Least Squares (OLS) and Generalized Method of Moments (GMM) on the ROA and ROE of the commercial banks of four of the ASEAN 5 countries, namely Malaysia, Philippines, Singapore, and Thailand from 2008-2021. Lagged ROA and ROE, GDP growth rate, inflation rate, and bank Z-Score were included as controls. The results of the study show that financial inclusion is positively associated with bank profitability. The results indicate that an increase in financial inclusion is associated with an increase in the ROA. Institutional quality increases ROE but negatively moderates the relationship between financial inclusion and the ROA. Additionally, the study finds that the controlled variables GDP, Inflation Rate, and Z-Score all have a contributing effect on commercial banks' ROA.